Wege bereiten, vermitteln und Denkräume schaffen! Reflexionen zu institutionellen und infrastrukturellen Erfolgsfaktoren für Digital Humanities an deutschen Universitäten auf Grundlage von Expert*inneninterviews - Ulrike Wuttke (Zeitschrift für digitale Geisteswissenschaften, 2022)
This article uses the example of the ›university‹ to illustrate which institutional framework conditions the Digital Humanities need in order to release innovation potential and to take on a leading role in the digital transformation of the Humanities. The focus of the discussion is on the consideration of the Digital Humanities as a community-induced phenomenon and the resulting important role of induction (i.e. of pioneers and mediators) and incubation (i.e. institutional spaces for thought and encounter). Taking the above as a starting point, it will also be explored to what extent this approach can be made fruitful for other institutional contexts.